Políticas públicas de efetivação da mediação pelo poder judiciário e o direito fundamental de acesso à justiça no Brasil - Santos, Ricardo Goretti (2018)
The purpose of this study is to verify whether the Public Policies of the dissemination of mediation adopted by the Brazilian Judiciary Power may contribute to the effectiveness of the fundamental right of access to justice in Brazil. In theoretical terms, this study is centered in dialectical thinking. In methodological terms, it is oriented by Karl Raymund Popper’s hypothetical-deductive method, which subsidizes the development of distortion tests of the motivating conjectures of the analyzed policies. It is structured in four chapters. Chapter I, named The society in the fluid modernity and its crisis, is about two sides of a global tension that characterizes the contemporary Brazilian society, creating a fertile scenario for the development of mediation. The two sides are: i) the crisis of intersubjective relations (analyzed under the theoretical references of Zygmunt Bauman and Edgar Morin); and ii) the crisis of conflict management (analyzed under the theoretical references of Sigmund Freud, Ingeborg Maus, Boaventura de Sousa Santos, ChaïmPerelman, Mauro Cappelletti, Carlos Henrique Bezerra Leite and Frank Ernest Arnold Sander). At this stage, in order to contribute to the development of the adequate conflict management practices, this study innovates by proposing rational and objective criteria to guide the choice of the most adequate method to the particularities of each concrete case. Chapter II, named Conflict mediation, refers to the philosophical and conceptual fundaments of this research, referring to Jean-Marie Muller, Luis Alberto Warat, Edgar Morin and Emmanuel Lévinas. Chapter III, named Public policies of mediation effectiveness as a way to access justice in Brazil, analyzes its institutionalization process: from the first Project of Law dedicated to this theme to its regulation by Resolution no 125/2010 from CNJ, the CPC/2015 and the Law no 13.140/2015. Chapter IV, named Conditions to mediation effectiveness as a way to access justice in Brazil, proposes six conditions to be observed in order to disseminate mediation in the Brazilian Judicial scenario, with potential contribution to guarantee the right of access to justice in Brazil. Finally, this research concludes that the Public Policies analyzed can contribute to the effectiveness of the fundamental right of access to justice in Brazil if the following conditions are observed: i – the provision of financial and human resources to implement and maintain the activities of Cejuscs; ii – the designation of at least one server for Cejusc, able to conduct the sorting of conflicts and to choose the adequate method to the particularities of each concrete case; iii – the qualification of mediators to the technical practice of the function; iv – the integration among different organs and institutions; v – the qualitative evaluation of the results of the service performed by the judicial mediators; vi – the overcoming of the judicialization prototype and the consequent formation of a culture of mediation in society and among the professionals of Law, by developing a pedagogy of mediation applied in the school environment and in the teaching of Law, based on the ethics of alterity and responsibility, on the co-existential management of conflicts in an autonomous, dialogue-oriented and non violent manner.